Pengembangan Harga Diri Anak Usia Dini - Dewi, Novi Cahya (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2015)
Self-esteem is not a factor brought about by birth, but it is a factor learned and shaped throughout the individual's experience, developing self-esteem means developing the belief that one is able to live and deserve to be happy in the face of life with confidence, virtue and optimism, helping to achieve goals. Developing self-esteem means expanding capacity for happiness. Parental involvement in instilling the child's personality from an early age is the domain of the educational environment within the family, since the primary foundation that generates the child's self-esteem is the parent who responds to the child's conditions and needs relevant to the child's self-esteem development.